2017
DOI: 10.1007/s12094-017-1685-3
|View full text |Cite
|
Sign up to set email alerts
|

Tumor infiltrating lymphocytes in acral lentiginous melanoma: a study of a large cohort of cases from Latin America

Abstract: ALM is highly prevalent in Peru and carries poor outcome. Lower TIL levels were associated with poor outcome and ALM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 59 publications
3
28
0
Order By: Relevance
“…This is in accordance with the research conducted by Castaneda et al . [ 16 ] In that study, it was stated that TILs in acral MM were fewer in number compared to in other MM types and this corresponded to the depth of invasion, progression rate and survival rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in accordance with the research conducted by Castaneda et al . [ 16 ] In that study, it was stated that TILs in acral MM were fewer in number compared to in other MM types and this corresponded to the depth of invasion, progression rate and survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…PD-L1 staining in membranes and in the cytoplasm was assessed on a semi-quantitative scale: positive when stained area was ≥ 5% and negative when < 5% ( Fig. 2 ) [ 16 ]. The number of CD8 + T cells was assessed by counting the number lymphocytes stained brown on the tumor cell membrane by an anti-CD8 antibody.…”
Section: Methodsmentioning
confidence: 99%
“…Under physiological and stroke conditions, new functional neurons integrate into the hippocampal network. Studies have shown a correlation between adult neurogenesis and re-learning for solving tasks in similar spatial environments [43][44][45][46]. The need for new neurons in spatial memory has been shown in studies using various ablation models to suppress neurogenesis [14].…”
Section: Discussionmentioning
confidence: 99%
“…While an association between NM and recurrence has been described [12], to our knowledge we are the first to identify ALM as an independent predictor of recurrence in patients with negative SLNs. Since both NM and ALM are associated with lower levels of tumor infiltrating lymphocytes, which are known to correlate with poor outcomes in melanoma, it is possible that differences in the immunogenicity of the primary melanoma are relevant for recurrence after negative SLNB [13,14]. Similarly, changes in the tumor microenvironment in ulcerated melanoma might explain why ulceration is associated with overall recurrence in patients with negative SLNs, since ulcerated melanoma may interact differently with the immune system [15].…”
mentioning
confidence: 99%